Natural Law: Source of Legitimacy of State Power in the Hobbesian Conception (2008)
The Hobbesian theory of knowledge, apart from being an interpretation of nature and its phenomena, is a theory on the legitimacy of state power. The hypothesis on the state of nature and on anthropology, originated there from, are categories allowing the